2021
DOI: 10.1177/14574969211030118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical drain output monitoring on patient outcomes in hepatopancreaticobiliary surgery: A systematic review

Abstract: Background and objective: Surgical drains are widely utilized in hepatopancreaticobiliary surgery to prevent intra-abdominal collections and identify postoperative complications. Surgical drain monitoring ranges from simple-output measurements to specific analysis for constituents such as amylase. This systematic review aimed to determine whether surgical drain monitoring can detect postoperative complications and impact on patient outcomes. Methods: A systematic review was performed, and the following databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Kowal et al pointed out that a rise in TBIL after surgery may not only show a higher chance of an early biliary stula but also cause cholestasis after surgery, which can cause infections aggravatingly and worsen patients' prognosis [27]. Studies have shown that postoperatively elevated serum TBIL may help predict the development of severe POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Kowal et al pointed out that a rise in TBIL after surgery may not only show a higher chance of an early biliary stula but also cause cholestasis after surgery, which can cause infections aggravatingly and worsen patients' prognosis [27]. Studies have shown that postoperatively elevated serum TBIL may help predict the development of severe POPF.…”
Section: Discussionmentioning
confidence: 99%